Microwave absorbing materials and molded articles for automotive radar sensor applications

By using a composite material composed of thermoplastic resin and carbon-based filler, the problem of automobile radar sensors being vulnerable to damage when facing microwave electromagnetic radiation is solved, and efficient microwave shielding and absorption effects are achieved.

CN115023461BActive Publication Date: 2025-02-18SHPP GLOBAL TECH BV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080094790.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-31
Filing Date
2020-12-31
Publication Date
2025-02-18
Estimated Expiration
2040-12-31

AI Technical Summary

Technical Problem

Existing automotive radar sensors are susceptible to damage when facing microwave electromagnetic radiation, and the commonly used metal shielding materials are heavy, expensive and complex to process.

Method used

Develop a composite material, including 50 wt.% to 90 wt.% thermoplastic resins (such as polycarbonate polysiloxane copolymers) and 10 wt.% to 50 wt.% carbon-based fillers with appropriate dielectric constants and Dissipation loss to achieve microwave shielding and absorption effects.

Benefits of technology

The composite material can absorb at least 60% of incident microwave radiation in the frequency range of 2-30GHz and at least 50% in the frequency range of 70GHz to 120GHz, significantly improving the shielding efficiency of automotive radar sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115023461B_ABST
    Figure CN115023461B_ABST
Patent Text Reader

Abstract

A composite is disclosed, comprising: about 50 wt.% to about 90 wt.% of a thermoplastic resin, wherein the thermoplastic resin comprises a polycarbonate polysiloxane copolymer; and about 10 wt.% to about 50 wt.% of a carbon-based filler. The composite exhibits a dielectric constant ε′ between 5 and 20 and a dissipation loss ε″ between 0.1 and 6 measured at a frequency between about 10 GHz and 120 GHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to materials that exhibit microwave absorptive properties, and in particular to materials that exhibit microwave absorptive properties for automotive radar sensor applications. Background Art

[0002] The automotive industry is increasingly adopting electronic radar sensors to provide driver assistance functions such as adaptive cruise control, parking / lane change assistance, reversing warning, blind spot detection, collision avoidance, etc. To ensure the correct operation of these sensors, these devices must be protected from potential sources of spurious electromagnetic radiation. Microwave radiation with a frequency of about 1 GHz (300 mm wavelength) to 300 GHz (1 mm wavelength) is the most common source of electromagnetic energy in the operation of radar sensors used in automotive applications. Metals (aluminum, stainless steel, etc.), polymer composite materials containing metal fillers, such as aluminum flakes, stainless steel fibers and silver-coated polyamide fibers, metallized coatings, inherently conductive polymers (polyacetylene, polypyrrole, polythiophene, polyaniline, etc.), silicon carbide, ferrites (Fe 2 O 3 +Ni / Zn / Cd / Co oxides) and carbonyl iron are some of the materials used to protect automotive radar sensors from destructive microwave electromagnetic radiation.

[0003] Metal is the most common material used for microwave (MW) shielding, but it is heavy and expensive. Metal also requires complex processing to be formed into the final component. Polymers or carbon composites are usually preferred because of their lower density, lower cost, ease of forming and ease of manufacturing into large-scale molded parts. Further, carbon fillers can be used in the composite to capture microwave radiation in the housing wall, thereby protecting the electronic sensors in the cavity. Moderate electrical conductivity and large dielectric and magnetic losses are generally required for materials used for microwave shielding.

[0004] Aspects of the present disclosure address these and other needs. Summary of the invention

[0005] Aspects of the present disclosure relate to a composite comprising: about 50 wt.% to about 90 wt.% of a thermoplastic resin, wherein the thermoplastic resin comprises a polycarbonate polysiloxane copolymer; and about 10 wt.% to about 50 wt.% of a carbon-based filler, wherein the composite exhibits a dielectric constant ε′ between 5 and 20 and a dissipation loss ε″ between 0.1 and 6 measured at a frequency between about 10 GHz and 120 GHz. The combined weight percentage values ​​of all components do not exceed 100 wt.%, and all weight percentage values ​​are based on the total weight of the composite. BRIEF DESCRIPTION OF THE DRAWINGS

[0006] Figure 1 Table 1 is presented containing formulations of CE1-CE5 and E1-E5.

[0007] Figure 2 Table 2 containing the surface resistivity and volume resistivity of CE1-CE5 and E1-E5 is presented.

[0008] Figure 3 A graphical representation of the volume resistivity of CE1-CE5 and E1-E5 is shown.

[0009] Figure 4 Shown is a graphical representation of the volume resistivity of samples CE1-CE5 and E1-E5 when the carbon black loading is adjusted.

[0010] Figure 5A and 5B Plots of the transmission mode and metal backing reflection mode of the free space method for determining the dielectric constant ε′ and dissipation losses ε″, respectively, are presented.

[0011] Figure 6 A graphical representation of the dielectric constant (ε′, the real part of the complex dielectric constant) of CE1 - CE5 and E1 - E5 at frequencies from 18 GHz to 26.5 GHz is shown.

[0012] Figure 7 A graphical representation of the dielectric losses (ε′, the imaginary part of the complex dielectric constant) of CE1-CE5 and E1-E5 at frequencies from 18 GHz to 26.5 GHz is shown.

[0013] Figure 8 A graphical representation of the return loss (front side of the panel) obtained for CEl-CE5 and E1-E5 in metal backing reflection mode at frequencies from 18 GHz to 26.5 GHz is shown.

[0014] Fig. 9 A graphical representation of the return loss (back side of the board) obtained for CE1-CE5 and E1-E5 in metal backing reflection mode at frequencies from 18 GHz to 26.5 GHz is shown.

[0015] Fig.10 A graphical representation of the attenuation constant values ​​for CE1-CE5 and E1-E5 at frequencies from 18 GHz to 26.5 GHz is shown.

[0016] Fig.11 A graphical representation of the overall shielding effectiveness (SE) values ​​for CE1-CE5 and E1-E5 at frequencies from 18 GHz to 26.5 GHz is shown.

[0017] Fig.12Shown is a graphical representation of the percentage of absorbed power obtained in transmission mode for samples CE1-CE5 and E1-E5 at frequencies from 18 GHz to 26.5 GHz.

[0018] Fig.13 A graphical representation of the percentage of absorbed power obtained in metal backing reflection mode at frequencies from 18 GHz to 26.5 GHz for samples CE1-CE5 and E1-E5 is shown.

[0019] Fig.14 A graphical representation of the dielectric constant (ε′, the real part of the complex dielectric constant) and dielectric loss (ε″, the imaginary part of the complex dielectric constant) of CE1-CE5 and E1-E5 at frequencies from 75 GHz to 110 GHz is shown.

[0020] Fig.15 A graphical representation of the return loss (front side of the panel) obtained for CE1-CE5 and E1-E5 in metal backing reflection mode at frequencies from 75 GHz to 110 GHz is shown.

[0021] Fig.16 A graphical representation of the attenuation constant values ​​for CE1-CE5 and E1-E5 at frequencies from 75 GHz to 110 GHz is shown.

[0022] Fig.17 A graphical representation of the overall shielding effectiveness (SE) values ​​for CE1-CE5 and E1-E5 at frequencies from 75 GHz to 110 GHz is shown.

[0023] Fig.18 A graphical representation of the percentage of power in transmission mode for sample CE1 at frequencies from 75 GHz to 110 GHz is shown.

[0024] Fig.19 A graphical representation of the percentage of power in transmission mode for sample CE2 at frequencies from 75 GHz to 110 GHz is shown.

[0025] Fig. 20 A graphical representation of the percentage of power in transmission mode for sample CE3 at frequencies from 75 GHz to 110 GHz is shown.

[0026] Fig.21 A graphical representation of the percentage of power in transmission mode for sample CE4 at frequencies from 75 GHz to 110 GHz is shown.

[0027] Fig. 22 A graphical representation of the percentage of power in transmission mode for sample CE5 at frequencies from 75 GHz to 110 GHz is shown.

[0028] Fig.23A graphical representation of the percentage of power in transmission mode for sample El at frequencies from 75 GHz to 110 GHz is shown.

[0029] Fig.24 A graphical representation of the percentage of power in transmission mode for sample E2 at frequencies from 75 GHz to 110 GHz is shown.

[0030] Fig.25 A graphical representation of the percentage of power in transmission mode for sample E3 at frequencies from 75 GHz to 110 GHz is shown.

[0031] Fig.26 A graphical representation of the percentage of power in transmission mode for sample E4 at frequencies from 75 GHz to 110 GHz is shown.

[0032] Fig. 27 A graphical representation of the percentage of power in transmission mode for sample E5 at frequencies from 75 GHz to 110 GHz is shown.

[0033] Fig.28A and 28B The values ​​of real and imaginary dielectric constants, dissipation factor, attenuation constant, total shielding effectiveness, power in transmission mode, and absorbed power for E1 to E5 at 77 GHz and 110 GHz, respectively, are shown.

[0034] Figures 29A to 29F It is a graphical representation of the real and imaginary dielectric constants, dissipation factor, attenuation constant, total shielding effectiveness, power in transmission mode, and absorbed power for E1 to E5 at 77 GHz.

[0035] Figures 30A to 30F It is a graphical representation of the real and imaginary dielectric constants, dissipation factor, attenuation constant, total shielding effectiveness, power in transmission mode, and power absorbed for E1 to E5 at 110 GHz. DETAILED DESCRIPTION

[0036] The present disclosure relates to microwave shielding and absorptive composite materials. Electronic radar sensors are used in the automotive industry to assist drivers with a variety of operations, including cruise control, lane change assistance, automatic parking, and blind spot detection. These sensors must be protected from electromagnetic interference that could impair their normal operation. Metals such as aluminum and stainless steel are commonly used as microwave shielding materials, but they are heavy, expensive, and require complex processing to be formed into final components. Polymer / carbon composites may be more desirable as lower density, lower cost alternatives. Polymer / carbon composites are also easier to mold and manufacture into large-volume molded parts. The carbon filler of the composite can isolate microwave radiation in the housing wall to protect the electronic sensor inside the cavity.

[0037] Therefore, moderate electrical conductivity and large dielectric and magnetic losses are some of the characteristics required of materials for microwave shielding. The present disclosure provides a series of polymer-based materials that include carbon as a microwave absorbing filler and whose polymer / filler ratio provides a proper balance between electrical conductivity and microwave absorption efficiency.

[0038] As demonstrated herein, composites with relatively high conductivity (corresponding to a volume resistivity of less than 100 Ohm.cm) behave dielectrically like metals and are therefore microwave reflective rather than microwave absorbing. Radar absorbing materials are currently sold commercially primarily in the form of elastomer-based flexible sheets or blankets, liquid coatings, and closed-cell polymer foams. The present disclosure provides rigid and high modulus thermoplastic-based carbon-filled materials that maintain a certain shape when molded and are suitable as internal or external components to capture or isolate electromagnetic radiation in automotive sensor applications.

[0039] Carbon fillers, including but not limited to powders, flakes, fibers, nanotubes are currently used to impart electromagnetic interference properties to polymers that are mostly transparent (non-absorbing, non-reflective) to microwave radiation when not filled with the carbon fillers. For example, when used in an automotive housing under the hood, a polymer-carbon composite can protect a radar sensor positioned inside the housing, thereby preventing electromagnetic radiation from the outside or even inside from degrading the electronic performance of the sensor. Moreover, carbon-containing elastomers, such as silicones, polyurethanes, and nitrile rubbers, can be used as high-loss protective blankets to attenuate the resonant frequencies generated by the normal operation of the sensor inside the cavity. The present disclosure describes a rigid, high-modulus, thermoplastic-based carbon-filled material that maintains a certain shape when molded and can be used as an internal or external component to capture electromagnetic radiation in automotive sensor applications.

[0040] Before disclosing and describing the disclosed compounds, compositions, articles, systems, devices and / or methods, it should be understood that they are not limited to specific synthetic methods unless otherwise specified, or to specific reagents unless otherwise specified, and thus they can certainly be varied. It should also be understood that the terminology used herein is only for the purpose of describing specific aspects and is not intended to be limiting.

[0041] The present disclosure encompasses various combinations of elements of the present disclosure, such as combinations of elements from dependent claims dependent upon the same independent claim.

[0042] Furthermore, it should be understood that any method described herein is in no way intended to be construed as requiring that its steps be performed in a particular order unless otherwise expressly stated. Therefore, in the event that a method claim does not actually recite the order in which its steps are to be followed or the steps are not otherwise specifically stated in the claims or specification to be limited to a particular order, no order is intended to be inferred in any respect. This applies to any possible non-express basis for interpretation, including: matters of logic with respect to the arrangement of steps or operational flow; plain meaning derived from grammatical organization or punctuation; and the number or type of embodiments described in the specification.

[0043] Compound

[0044] Aspects of the present disclosure relate to a composite comprising a thermoplastic polymer component (comprising a polycarbonate-polysiloxane copolymer) and a carbon filler. The thermoplastic polymer component may comprise any suitable thermoplastic polymer. Examples include, but are not limited to, polycarbonates, polyetherimides, liquid crystal polymers, polyamides, polyimides, polyesters, copolymers thereof, blends thereof, or combinations thereof.

[0045] In certain aspects, the composite has a surface resistivity greater than 100 Ohm / square and a volume resistivity greater than 1000 Ohm.cm when measured according to ASTM D257 using a sample having a thickness of 0.125 inches (3.175 mm). Further, the composite can exhibit a dielectric constant Dk (real part ε′ of the complex dielectric constant) of about 5 to about 35 and exhibit dissipative losses (imaginary part ε″ of the complex dielectric constant) of about 0.1 to about 5. The ratio of dissipative losses to the dielectric constant ε″ / ε′ of the composite (referred to as the dissipation factor Df or tan δ) can be about 0.003 to about 1.

[0046] The molded panels formed from the disclosed composites may be suitable as external components or internal components of electronic devices for microwave absorption or shielding applications. Experiments have shown that panels molded from the materials of the present invention are capable of absorbing at least 60% of incident microwave radiation somewhere in the range of 2-30 GHz (-4 dB reflection loss), while the absorption bandwidth of at least 0.5 GHz of radiation is at -10 dB (90% absorption efficiency). The thickness of the molded panels may be from 1 millimeter (mm) to about 5 mm. In various examples, the thickness of the molded panels may be 0.125 inches (in).

[0047] In various aspects, the present disclosure provides composite materials that can be used to make housings that can electromagnetically isolate electronic sensors from destructive microwaves. Dielectric properties of these materials, such as complex permittivity, reflection and insertion loss, attenuation and shielding effectiveness, etc., have been evaluated at frequencies of about 10 GHZ to 110 GHz. Further disclosed herein are radar sensor components (boards, housings, covers, etc.) made from these materials, as well as articles (sensors, cameras, electronic control units (ECUs)) made from these components.

[0048] Further disclosed is a component of an automotive radar sensor, such as a plate, housing or cover, which is molded from a material including a polymer and a carbon filler, wherein the molded part has a certain design, average thickness, microwave absorption efficiency, absorption bandwidth and a certain surface resistivity / volume resistivity. Still another aspect of the present disclosure is an article, such as a radar sensor, a camera, an ECU, which includes a molded part made of a radar absorbing material, wherein such a molded part has at least two openings to allow transmission of microwave radiation between a transmitting antenna and a receiving antenna positioned in a printed circuit board of the sensor. Automotive radar sensors used for lane change assistance, automatic parking, blind spot detection and collision avoidance typically operate at a frequency of 24 GHz; those automotive radar sensors used for adaptive cruise control operate at a frequency of 77 GHz. Therefore, the composites of the present disclosure have been observed in the K band containing a frequency of 24 GHz and in the W band containing a frequency of 77 GHz.

[0049] Polymer matrix resin

[0050] On the one hand, polymer composition can include polymer matrix resin.In various fields, polymer matrix resin can include thermoplastic resin or thermosetting resin.Thermoplastic resin can include polypropylene, polyethylene, copolymer based on ethylene, polyamide, polycarbonate, polyester, polyoxymethylene (POM), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polycyclohexylene dimethyl terephthalate (PCT), liquid crystal polymer (LPC), polyphenylene sulfide (PPS), polyphenylene oxide (PPE), polyphenylene oxide-polystyrene blend, polystyrene, high impact modified polystyrene, acrylonitrile-butadiene-styrene (ABS) terpolymer, acrylic polymer, polyetherimide (PEI), polyurethane, polyetheretherketone (PEEK), polylactic acid (PLA) base polymer, polyethersulfone (PES) and combination thereof.Thermoplastic resin can also include thermoplastic elastomer, such as polyamide and polyester-based elastomer.Base material can also include blend and / or other types of combination of above-mentioned resin. In various aspects, the polymer matrix resin may also include a thermosetting polymer. Suitable thermosetting resins may include phenolic resins, urea-formaldehyde resins, melamine-formaldehyde resins, urea-formaldehyde latex, xylene resins, phthalate bisacrylic resins, epoxy resins, aniline resins, furan resins, polyurethanes, or combinations thereof.

[0051] The polymeric base resin of the present disclosure may comprise a polyamide resin or a combination of polyamide resins. Polyamide resins useful in practicing the present invention comprise a class of resins known as nylons, which are characterized by the presence of an amide group (-C(O)NH-). Also suitable for the present method are polyphthalamide (PPA) polyamides including, but not limited to, polyamide-6, polyamide-6,6, polyamide-4,6, polyamide 9T, polyamide 10T, polyamide-11, polyamide-12, polyamide-6,10, polyamide-6,12, polyamide 6 / 6,6, polyamide-6 / 6,12, polyamide MXD6, polyamide-6T, polyamide-6I, polyamide-6 / 6T, polyamide-6 / 6I, polyamide-6,6 / 6T, polyamide-6,6 / 6I, polyamide-6 / 6 / 176I, polyamide-6,6 / 6T / 6I, polyamide-6 / 12 / 6T, polyamide-6,6 / 12 / 6T, polyamide-6 / 12 / 6I, polyamide-6,6 / 12 / 6I and combinations thereof. Nylon-6 and nylon-6,6 represent common polyamides and are available from a variety of commercial sources. However, polyamides such as nylon-4,6, nylon-12, nylon-6,10, nylon 6,9, nylon 6 / 6T and nylon 6,6 / 6T having a triamine content of less than about 0.5 wt.%, and others such as amorphous nylons may also be used. In an example, the polymer composition includes polyamide-6.

[0052] Polycarbonates and combinations thereof may also be used as polymer matrix resins. As used herein, "polycarbonate" refers to an oligomer or polymer comprising one or more dihydroxy compounds, such as residues of dihydroxy aromatic compounds, connected by carbonate bonds; it also encompasses homopolycarbonates, copolycarbonates and (co) polyester carbonates. Throughout the specification, the terms "residue" and "structural unit" used with respect to the components of the polymer are synonymous.

[0053] In certain aspects, the polycarbonate polymer is bisphenol A polycarbonate, a high molecular weight (Mw) high flow / ductility (HFD) polycarbonate, a low Mw HFD polycarbonate, or a combination thereof.

[0054] As used herein, the terms "BisA," "BPA," or "bisphenol A," which may be used interchangeably, refer to a compound having a structure represented by formula (1):

[0055]

[0056] BisA may also be referred to by the name 4,4'-(propane-2,2-diyl)diphenol; p,p'-isopropylidenebisphenol; or 2,2-bis(4-hydroxyphenyl)propane. BisA has CAS# 80-05-7.

[0057] In one example, the composite can include a linear general-purpose polycarbonate homopolymer resin, such as PC 105, a 100-grade polycarbonate powder available from SABIC. In another example, the composite can include a linear high-flow polycarbonate available from SABIC, such as ML5221, a linear polycarbonate having a melt flow rate of 25 grams per 10 minutes (g / 10 minutes) when tested according to ASTM D1238. High-flow polycarbonate can refer to a polycarbonate having a flow rate of at least about 15 g / 10 minutes, or at least about 18 g / 10 minutes, or at least about 20 g / 10 minutes when tested according to ASTM D1238.

[0058] In addition to the above-mentioned polycarbonates, combinations of polycarbonates with other thermoplastic polymers, such as homopolycarbonates, copolycarbonates, and combinations of polycarbonate copolymers with polyesters, can be used. Useful polyesters include, for example, poly(dicarboxylic acid alkylene esters), liquid crystal polyesters, and polyester copolymers. When blended, the polyesters described herein are generally fully miscible with the polycarbonates.

[0059] A combination of a first and a second (or more) polycarbonate-polysiloxane copolymer may be used, wherein the average value of E of the first copolymer is less than the average value of E of the second copolymer.

[0060] In one aspect, the polydiorganosiloxane block has formula (2)

[0061]

[0062] wherein E is as defined above; each R may be the same or different and is as defined above; and Ar may be the same or different and is substituted or unsubstituted C 6 -C 30 Arylene, wherein the bond is directly attached to the aromatic moiety. The Ar group in formula (2) can be derived from C 6 -C 30 Dihydroxyarylene compounds, for example dihydroxyarylene compounds. Dihydroxyarylene compounds are 1,1-bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)n-butane, 2,2-bis(4-hydroxy-1-tolyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl sulfide) and 1,1-bis(4-hydroxy-tert-butylphenyl)propane. Combinations comprising at least one of the foregoing dihydroxy compounds may also be used.

[0063] In another aspect, the polydiorganosiloxane block may have formula (3)

[0064]

[0065] wherein R and E are as described above, and each R5 is independently a divalent C 1 -C 30 In one aspect, the polydiorganosiloxane block has the formula (5):

[0066]

[0067] wherein R and E are as defined above. 6 It is a two-price C 2 -C 8 In formula (4), each M may be the same or different and may be halogen, cyano, nitro, C 1 -C 8 Alkylthio, C 1 -C 8 Alkyl, C 1 -C 8 Alkoxy, C 2 -C 8 Alkenyl, C 2 -C 8 Alkenyloxy, C 3 -C 8Cycloalkyl, C 3 -C 8 Cycloalkoxy, C 6 -C 10 Aryl, C 6 -C 10 Aryloxy, C 7 -C 12 Aralkyl, C 7 -C 12 Aralkyloxy, C 7 -C 12 Alkyl aryl or C 7 -C 12 Alkylaryloxy, wherein each n is independently 0, 1, 2, 3 or 4.

[0068] In one aspect, M is bromo or chloro, alkyl, such as methyl, ethyl or propyl, alkoxy, such as methoxy, ethoxy or propoxy, or aryl, such as phenyl, chlorophenyl or tolyl; R 6 is dimethylene, trimethylene or tetramethylene; and R is C 1-8 In another embodiment, R is methyl, or a combination of methyl and trifluoropropyl, or a combination of methyl and phenyl. In still another embodiment, R is methyl, M is methoxy, n is one, and R 6 For divalent C 1 -C 3 Aliphatic groups. Specific polydiorganosiloxane blocks have the formula:

[0069]

[0070] Or a combination comprising at least one of the foregoing, wherein E has an average value of 2 to 200, 2 to 125, 5 to 125, 5 to 100, 5 to 50, 20 to 80, or 5 to 20.

[0071] The blocks of formula (4) can be derived from the corresponding dihydroxy polydiorganosiloxanes, which in turn can be prepared by platinum-catalyzed addition between siloxane hydrides and aliphatic unsaturated monophenols such as eugenol, 2-alkylphenols, 4-allyl-2-methylphenol, 4-allyl-2-phenylphenol, 4-allyl-2-bromophenol, 4-allyl-2-tert-butoxyphenol, 4-phenyl-2-phenylphenol, 2-methyl-4-propylphenol, 2-allyl-4,6-dimethylphenol, 2-allyl-4-bromo-6-methylphenol, 2-allyl-6-methoxy-4-methylphenol and 2-allyl-4,6-dimethylphenol. The polysiloxane-polycarbonate copolymer can then be made, for example, by the synthetic procedure of European Patent Application Publication No. 0 524 731 A1 to Hoover, page 5, Preparation 2.

[0072] The transparent polysiloxane-polycarbonate copolymer may include carbonate units (1) derived from bisphenol A and repeating siloxane units or a combination including at least one of the foregoing, specifically having Formula 4a, wherein the average value of E is 4 to 50, 4 to 15, specifically 5 to 15, more specifically 6 to 15, and still more specifically 7 to 10. The transparent copolymer may be made using one or both of the tubular reactor methods described in U.S. Patent Application No. 2004 / 0039145A1, or the poly(siloxane-carbonate) copolymer may be synthesized using the method described in U.S. Patent No. 6,723,864.

[0073] The polysiloxane-polycarbonate copolymer can include 50 wt.% to 99 wt.% carbonate units and 1 wt.% to 50 wt.% siloxane units. Within this range, the polyorganosiloxane-polycarbonate copolymer can include 70 wt.% to 98 wt.%, more specifically 75 wt.% to 97 wt.% carbonate units and 2 wt.% to 30 wt.%, more specifically 3 wt.% to 25 wt.% siloxane units.

[0074] In some aspects, blends may be used, specifically blends of bisphenol A homopolycarbonate of formula (5) and polysiloxane-polycarbonate block copolymers of bisphenol A blocks and eugenol-terminated polydimethylsiloxane blocks.

[0075]

[0076] wherein x is 1 to 200, specifically 5 to 85, specifically 10 to 70, specifically 15 to 65, and more specifically 40 to 60; y is 1 to 500 or 10 to 200, and z is 1 to 1000 or 10 to 800. In one embodiment, x is 1 to 200, y is 1 to 90 and z is 1 to 600, and in another embodiment, x is 30 to 50, y is 10 to 30 and z is 45 to 600. The polysiloxane blocks may be randomly distributed or controlled distributed in the polycarbonate blocks.

[0077] In one aspect, the polysiloxane-polycarbonate copolymer can include 10 wt% or less, specifically 6 wt% or less, and more specifically 4 wt% or less of polysiloxane, based on the total weight of the polysiloxane-polycarbonate copolymer, and can be generally optically transparent and can be commercially available from SABIC under the name EXL-T. On the other hand, the polysiloxane-polycarbonate copolymer can include 10 wt% or more, specifically 12 wt% or more, and more specifically 14 wt% or more of the polysiloxane copolymer, based on the total weight of the polysiloxane-polycarbonate copolymer, and is generally optically opaque and can be commercially available from SABIC under the trade name EXL-P.

[0078] The polyorganosiloxane-polycarbonate can have a weight average molecular weight of 2,000 to 100,000 Daltons, specifically 5,000 to 50,000 Daltons, as measured by gel permeation chromatography using a crosslinked styrene-divinylbenzene column at a sample concentration of 1 mg / mL and as calibrated with polycarbonate standards.

[0079] The polyorganosiloxane-polycarbonate may have a melt volume flow rate of 1 to 50 cubic centimeters per 10 minutes (cc / 10min), specifically 2 to 30 cc / 10min, measured at 300°C / 1.2kg. Mixtures of polyorganosiloxane-polycarbonates with different flow properties may be used to achieve the overall desired flow properties.

[0080] The non-limiting examples of polysiloxane-polycarbonate copolymers can include various copolymers available from SABIC. On the one hand, by the total weight of polysiloxane-polycarbonate copolymers, polysiloxane-polycarbonate copolymers can contain 6 weight % of polysiloxane content. In various aspects, the weight average molecular weight (Mw) of 6 weight % polysiloxane block copolymers can be about 23,000 to 24,000 daltons using gel permeation chromatography by bisphenol A polycarbonate absolute molecular weight standard. In certain aspects, 6 weight % siloxane polysiloxane-polycarbonate copolymers can have a melt volume flow rate (MVR) of about 10 cubic centimeters / 10 minutes at 300°C / 1.2kg (see C9030T, a copolymer of 6 weight % polysiloxane content, available as "transparent" EXL C9030T resin polymer purchased from SABIC Innovative Plastics). In another example, the polysiloxane-polycarbonate block may include 20% by weight of polysiloxane based on the total weight of the polysiloxane-polycarbonate block copolymer. For example, a suitable polysiloxane-polycarbonate copolymer may be a bisphenol A polysiloxane-polycarbonate copolymer (see C9030P, commercially available from SABIC as "opaque" EXLC9030P) terminated with p-cumylphenol (PCP) and having a polysiloxane content of 20%. In various aspects, the weight average molecular weight of the 20% polysiloxane block copolymer may be from about 29,900 Daltons to about 31,000 Daltons when tested on a cross-linked styrene-divinylbenzene column using gel permeation chromatography (GPC) according to polycarbonate standards and calibrated to a polycarbonate reference on a 1 mg / ml sample eluted at a flow rate of about 1.0 ml / minute using a UV-VIS detector set at 264 nm. Furthermore, the 20% polysiloxane block copolymer may have a melt volume rate (MVR) of 7 cc / 10 min at 300° C. / 1.2 kg and may exhibit siloxane domains ranging in size from about 5 microns to about 20 microns (μm).

[0081] As described herein, the polymer matrix resin may include a variety of thermoplastic resins or combinations thereof. In one example, the polymer matrix resin may include a polycarbonate copolymer containing units derived from BPA, or a mixture of one or more polycarbonate copolymers including units derived from BPA. In a specific example, the polymer matrix resin may include a polycarbonate copolymer having units derived from BPA and a poly(aliphatic ester)-polycarbonate copolymer derived from sebacic acid.

[0082] In a further example, the polycarbonate of the polymer matrix resin may include a branched polycarbonate. Exemplary branching agents may include, but are not limited to, 1,1,1-tris(4-hydroxyphenyl)ethane (THPE). As a further example, the branched polycarbonate resin may be end-capped with a suitable end-capping agent, such as p-cyanophenol (referred to as HBN).

[0083] Certain aspects of the composition comprise from about 5 wt.% to about 99 wt.% of a polymer matrix resin, or from about 40 wt.% to about 99 wt.% of a polymer matrix resin, or from about 55 wt.% to about 99 wt.% of a polymer matrix resin, or from about 60 wt.% to about 99 wt.% of a polymer matrix resin, or from about 70 wt.% to about 99 wt.% of a polymer matrix resin, or from about 40 wt.% to about 95 wt.% of a polymer matrix resin, or from about 55 wt.% to about 95 wt.% of a polymer matrix resin, or from about 60 wt.% to about 95 wt.% of a polymer matrix resin, or from about 75 wt.% to about 95 wt.% of a polymer matrix resin.

[0084] Carbon-based fillers

[0085] In various aspects, the polymer composition includes a filler based on carbon. Typically, a filler based on carbon can include carbon fibers, carbon powder, graphite, graphene, carbon flakes or carbon nanotubes. A filler based on carbon can further refer to a particulate carbonaceous material, such as furnace black, thermal black, surface modified carbon black, heat treated carbon black, activated carbon, graphite, carbon fibers, carbon nanotubes or a combination thereof. According to some aspects of the present disclosure, a filler based on carbon includes carbon powder. In addition, a filler based on carbon can include carbon powder and may be free of or substantially free of carbon nanotubes, carbon flakes or carbon fibers.

[0086] In one example, the carbon-based filler is carbon black. Carbon black can refer to amorphous carbon with a high surface area to volume ratio. Further, depending on the manufacturing conditions, carbon black can contain chemically adsorbed oxygen complexes (such as carboxyl, quinone, lactone, phenolic, etc.) on its surface to varying degrees. Carbon black properties, such as particle size, structure and purity may vary depending on the type of carbon black selected. On the one hand, carbon black can be well dispersed in the polymer phase, maintain the integrity of its structure or network, and have a consistent particle size.

[0087] The conductivity of the polymer-carbon black composite can be measured using the surface resistivity (SR) of the conductive film. In one aspect, the conductivity can depend on the polymer phase, the type of conductive carbon black, the loading of the conductive carbon black, and the dispersion of the conductive carbon black. The conductive carbon black can be furnace black or acetylene black or additional conductive carbon black. The high volume resistivity of conductive carbon blacks such as furnace black or acetylene black is in the range of 1 to 10 2Such carbon blacks may exhibit a BET (Brunauer, Emmett and Teller) surface area of ​​at least about 50 grams per square meter (m 2 / g). In another aspect, the carbon black powder exhibits an oil absorption of at least about 100 milliliters (ml) / 100 grams (g). In a specific aspect, the conductive filler includes ENSACO available from Earache Europe. TM 250 carbon powders, which have high to very high void volumes, allowing the carbon network to be maintained at low to very low filler levels.

[0088] In some aspects, the polymer composition can include a carbon-based filler having at least one dimension of a specific size. The carbon-based filler can include a powder having a specific particle size distribution. For example, at least one dimension of the carbon-based filler can be less than 100 nm.

[0089] In some aspects, the carbon-based filler can have a specific diameter. The polymer composition of claim 1, wherein the carbon-based filler can include a powder or a diameter less than 30 microns. In another example, the carbon-based filler has a diameter less than 10 microns.

[0090] In some aspects, based on the gross weight of the polymer composition, the composition can include about 0.01wt.% to about 50wt.% of a carbon-based filler. In other aspects, the composition can include about 0.01wt.% to about 5wt.%, or about 0.01wt.% to about 3wt.%, or about 0.1wt.% to about 3wt.%, or about 0.01wt.% to about 2.5wt.%, or about 0.5wt.% to about 3wt.% of a carbon-based filler, or about 1wt.% to about 3wt.% of a carbon-based filler or about 0.5wt.% to about 2.5wt.% of a carbon-based filler.

[0091] additive

[0092] The disclosed thermoplastic composition can include one or more additives conventionally used to make molded thermoplastic parts, provided that the optional additives do not adversely affect the desired properties of the resulting composition. Mixtures of optional additives can also be used. Such additives can be mixed at a suitable time during the mixing of the components used to form the composite mixture. Exemplary additives can include ultraviolet agents, ultraviolet stabilizers, heat stabilizers, antistatic agents, antimicrobial agents, anti-drip agents, radiation stabilizers, pigments, dyes, fibers, fillers, plasticizers, fibers, flame retardants, antioxidants, lubricants, wood, glass and metals, and combinations thereof.

[0093] According to certain aspects, the polymer composition can maintain mechanical properties and dielectric strength even with high levels of filler (eg, greater than 30 wt. % filler, based on the total weight of the polymer composition).

[0094] Thermoplastic compositions disclosed herein may include one or more additional fillers. Fillers may be selected to impart additional impact strength and / or provide additional features that may be based on the final selected features of the polymer composition. In some respects, fillers may include inorganic materials that may include clay, titanium oxide, asbestos fibers, silicates and silicon dioxide powders, boron powder, calcium carbonate, talcum, kaolin, sulfides, barium compounds, metals and metal oxides, wollastonite, glass spheres, glass fibers, flaky fillers, fiber fillers, natural fillers and reinforcing agents and reinforcing organic fiber fillers.

[0095] Suitable fillers or reinforcing agents may include, for example, mica, clay, feldspar, quartz, quartzite, perlite, diatomite, diatomaceous earth, aluminum silicate (mullite), synthetic calcium silicate, fused silica, fumed silica, sand, boron nitride powder, boron silicate powder, calcium sulfate, calcium carbonate (such as chalk, limestone, marble and synthetic precipitated calcium carbonate), talc (including fibrous, modular, acicular and lamellar talc), wollastonite, hollow or solid glass spheres, silicate spheres, cenospheres, aluminosilicates or armospheres, kaolin, silicon carbide, aluminum oxide, boron carbide, whiskers of iron, nickel or copper, continuous and chopped carbon fibers. The filler and reinforcing agent can be a composite of at least one of the filler and reinforcing agent. The filler and reinforcing agent can be a composite of at least one of the filler and reinforcing agent. The filler and reinforcing agent can be coated with, for example, silane or surface treated to improve adhesion and dispersibility with a polymer matrix. Based on 100 parts by weight of the total composition, the filler can be used in an amount of 1 to 200 parts by weight based on 100 parts by weight.

[0096] In some respects, the thermoplastic composition can include a synergist. In various examples, fillers can serve as flame retardant synergists. When added to the flame retardant composition, the synergist promotes the improvement of flame retardant properties, which is better than the comparative composition containing all the same ingredients of the same amount except the synergist. The example of the mineral filler that can be used as a synergist is mica, talc, calcium carbonate, dolomite, wollastonite, barium sulfate, silicon dioxide, kaolin, feldspar, barite, etc., or a combination including at least one of the aforementioned mineral fillers. Metal synergists such as antimony oxide can also be used together with flame retardants. In an example, the synergist can include magnesium hydroxide and phosphoric acid. The mineral filler can have an average particle size of about 0.1 to about 20 microns, specifically about 0.5 to about 10 microns, and more specifically about 1 to about 3 microns.

[0097] The thermoplastic composition may include an antioxidant. The antioxidant may include a primary antioxidant or a secondary antioxidant. For example, the antioxidant may include an organic phosphite, such as tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, distearylpentaerythritol diphosphite, etc.; alkylated monophenols or polyphenols; alkylation reaction products of polyphenols with dienes, such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid)]methane, etc.; butylation reaction products of p-cresol or dicyclopentadiene; alkylated hydroquinone; hydroxylated thiodiphenyl ether; alkylene-bisphenols; benzyl compounds; β-(3,5-di-tert-butyl) Esters of β-(5-tert-butyl-4-hydroxyphenyl)-propionic acid and monohydric alcohols or polyhydric alcohols; esters of β-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid and monohydric alcohols or polyhydric alcohols; esters of thioalkyl or thioaryl compounds such as distearyl thiodipropionate, didodecyl thiodipropionate, ditridecyl thiodipropionate, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid octadecyl ester, etc.; amides of β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, etc., or a combination comprising at least one of the foregoing antioxidants. The antioxidant can be generally used in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0098] In various aspects, the thermoplastic composition can include a release agent. Exemplary release agents can include, for example, metal stearates, stearyl stearate, pentaerythritol tetrastearate, beeswax, montan wax, paraffin wax, etc., or a combination comprising at least one of the foregoing release agents. The release agent is typically used in an amount of about 0.1 to about 1.0 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0099] In one aspect, the thermoplastic composition may include a heat stabilizer. As an example, the heat stabilizer may include, for example, an organic phosphite, such as triphenyl phosphite, tri-(2,6-xylyl)phosphite, tri-(mixed mono-nonylphenyl and di-nonylphenyl)phosphite, etc.; a phosphonate such as dimethylphenylphosphonate, a phosphate such as trimethyl phosphate, or a combination comprising at least one of the foregoing heat stabilizers. The heat stabilizer may generally be used in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0100] In a further aspect, a light stabilizer can be present in the thermoplastic composition. Exemplary light stabilizers can include, for example, benzotriazoles such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone, or a combination comprising at least one of the foregoing light stabilizers. The light stabilizer can generally be used in an amount of about 0.1 to about 1.0 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0101] The thermoplastic composition may also include a plasticizer. For example, the plasticizer may include a phthalate, such as dioctyl-4,5-epoxy-hexahydrophthalate, tris-(octyloxycarbonylethyl)isocyanurate, tristearin, epoxidized soybean oil, or the like, or a combination comprising at least one of the foregoing plasticizers. The plasticizer is typically used in an amount of about 0.5 to about 3.0 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0102] Ultraviolet (UV) absorbers may also be present in the disclosed thermoplastic compositions. Exemplary UV absorbers may include, for example, hydroxybenzophenones; hydroxybenzotriazoles; hydroxybenzotriazines; cyanoacrylates; oxalic acid anilides; benzoxazinones; 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-phenol (CYASORB TM 5411); 2-Hydroxy-4-N-octyloxybenzophenone (CYASORB TM 531); 2-[4,6-bis(2,4-xylyl)-1,3,5-triazine-2-yl]-5-(octyloxy)-phenol (CYASORB TM 1164); 2,2′-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) (CYASORB TM UV-3638); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane (UVINUL TM3030); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane; nanoscale inorganic materials, such as titanium oxide, cerium oxide and zinc oxide, each having a particle size of less than 100 nanometers; or the like, or a combination comprising at least one of the foregoing UV absorbers. The UV absorber is generally used in an amount of 0.01 to 3.0 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0103] The thermoplastic composition may further include a lubricant. As an example, the lubricant may include, for example, a fatty acid ester, such as an alkyl stearate, for example, methyl stearate, etc.; a mixture of methyl stearate with a hydrophilic and hydrophobic surfactant, the surfactant comprising a polyethylene glycol polymer, a polypropylene glycol polymer, and copolymers thereof, such as methyl stearate and a polyethylene glycol-polypropylene glycol copolymer in a suitable solvent; or a combination comprising at least one of the foregoing lubricants. The lubricant may generally be used in an amount of about 0.1 to about 5 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0104] Anti-drip agents may also be used in the composition, such as fibril-forming or non-fibril-forming fluoropolymers, such as polytetrafluoroethylene (PTFE). The anti-drip agent may be encapsulated by a rigid copolymer, such as styrene-acrylonitrile copolymer (SAN). PTFE encapsulated in SAN is referred to as TSAN. In one example, TSAN may include 50 wt.% PTFE and 50 wt.% SAN, based on the total weight of the encapsulated fluoropolymer. SAN may include, for example, 75 wt.% styrene and 25 wt.% acrylonitrile, based on the total weight of the copolymer. Anti-drip agents such as TSAN may be used in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the total composition excluding any filler.

[0105] As an example, the disclosed composition may include an impact modifier. The impact modifier may be a chemically reactive impact modifier. By definition, a chemically reactive impact modifier may have at least one reactive group such that when the impact modifier is added to a polymer composition, the impact resistance of the composition (expressed as an IZOD impact value) is improved. In some examples, the chemically reactive impact modifier may be an ethylene copolymer having reactive functional groups selected from, but not limited to, anhydride, carboxyl, hydroxyl, and epoxy.

[0106] In other aspects of the present disclosure, the composition may include a rubbery impact modifier. The rubbery impact modifier may be a polymer material that can substantially recover its shape and size after removing the force at room temperature. However, the rubbery impact modifier should generally have a glass transition temperature of less than 0°C. In certain aspects, the glass transition temperature (Tg) may be less than -5°C, -10°C, -15°C, wherein a Tg of less than -30°C generally provides better performance. Representative rubbery impact modifiers may include, for example, functionalized polyolefin ethylene-acrylate terpolymers, such as ethylene-acrylate-maleic anhydride (MAH) or glycidyl methacrylate (GMA). The functionalized rubbery polymer may optionally contain repeating units of monomers derived from anhydride groups such as maleic anhydride in its main chain. In another case, the functionalized rubbery polymer may contain anhydride moieties grafted onto the polymer in a post-polymerization step.

[0107] Features and products

[0108] In certain aspects, the disclosed composites can exhibit microwave absorption and shielding properties. A molded article or molded plate including the composite can exhibit a dielectric constant between 5 and 35 and a dissipation loss between 0.1 and 5. At a frequency of about 2 to about 30 GHz, the dissipation factor Df (tan δ, ε″ / ε′) can be between 0.003 and 1.

[0109] Plates molded from the disclosed composites can exhibit certain microwave absorption properties. For example, a molded plate having a thickness of about 0.125 inches (0.3125 cm) can absorb at least about 60% of incident microwave radiation at frequencies between 2 and 30 GHz, corresponding to a reflection loss of -4 decibels (dB), and an absorption bandwidth of at least 0.5 GHz of radiation at -10 dB (corresponding to 90% absorption efficiency). This performance may be evident for molded plates having a thickness between 1 mm and 5 mm. Plates molded from the disclosed composites can exhibit certain attenuation properties. Attenuation increases with increasing carbon. Attenuation increases (more negative values) with increasing amounts of siloxane (for the same amount of carbon), indicating energy loss, i.e., energy attenuation within the material. For example, attenuation values ​​of at least -5 dB / cm to about -30 dB / cm in the K-band and -10 dB / cm to about -90 dB / cm in the W-band were observed. At the same carbon content and frequency, these siloxane-containing composites show greater attenuation than their counterparts without siloxane. Plates molded from the disclosed composites can exhibit certain shielding properties. As the amount of carbon black increases, the total shielding may increase. In addition, when compared to the counterparts without siloxane, at the same carbon black content and frequency, siloxane can further improve the total shielding. For example, shielding effectiveness values ​​of at least 2dB to about 15dB in the K band and at least 5dB to 30dB in the W band were observed. These values ​​show that, surprisingly, polysiloxane helps carbon black capture more radiation than in the absence of polysiloxane.

[0110] In various aspects, the present disclosure relates to articles comprising the compositions herein. The compositions can be molded into useful shaped articles by various means, such as injection molding, extrusion, rotational molding, blow molding, and thermoforming to form articles. The compositions can be used to make articles requiring materials with good flowability, good impact strength, and good dielectric strength. In various aspects, the compositions can also be used for conductive purposes.

[0111] The advantageous features of the compositions disclosed herein may make them suitable for a range of uses.

[0112] Method for preparing the composite

[0113] Aspects of the present disclosure further relate to methods for preparing composites comprising thermoplastic polymer components. In many aspects, compositions can be prepared according to a variety of methods. The compositions of the present disclosure can be blended, compounded or otherwise combined with the aforementioned ingredients by a variety of methods, including intimate mixing of the material with any additional additives desired in the formulation. Due to the availability of melt blending equipment in commercial polymer processing facilities, melt processing methods can be used. In various other aspects, the equipment used in such melt processing methods can include but is not limited to co-rotating and counter-rotating extruders, single screw extruders, co-kneaders, disc stack processors and various other types of extrusion equipment. In other aspects, the extruder is a twin screw extruder. In various other aspects, the composition can be processed in an extruder at a temperature of about 180°C to about 350°C, specifically 250°C to 300°C.

[0114] The method may further include treating the composite to provide a plate with a desired thickness. The plate may be extruded, injection molded, compression molded or injection compression molded, and the thickness may be between about 0.5 mm and 6 mm. Other processes may also be applied to thermoplastic films, including but not limited to lamination, coextrusion, thermoforming or hot pressing. In this respect, additional layers of other materials (e.g., other thermoplastic polymer layers, metal layers, etc.) may be combined with the composite.

[0115] The present disclosure encompasses various combinations of elements of the present disclosure, such as combinations of elements from dependent claims dependent upon the same independent claim.

[0116] definition

[0117] It should also be understood that the terminology used herein is for the purpose of describing particular aspects only and is not intended to be limiting. As used in the specification and claims, the term "comprising" may include embodiments of "consisting of" and "consisting essentially of". Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. In this specification and the claims that follow, reference will be made to a number of terms that shall be defined herein.

[0118] As used in the specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a thermoplastic polymer component" includes a mixture of two or more thermoplastic polymer components. As used herein, the term "combination" includes blends, mixtures, alloys, reaction products, and the like.

[0119] Scope can be expressed as from a value (first value) to another value (second value) in this article. When expressing such a scope, the scope includes one or both of the first value and the second value in some aspects. Similarly, when a value is expressed as an approximate value by using the antecedent "about", it should be understood that the specific value forms another aspect. It should be further understood that the endpoints of each scope are effective in relation to and independently of the other endpoint. It should also be understood that multiple values ​​are disclosed herein, and each value is also disclosed herein as "about" for the specific value in addition to the value itself. For example, if the value "10" is disclosed, "about 10" is also disclosed. It should also be understood that each unit between two specific units is also disclosed. For example, if 10 and 15 are disclosed, 11, 12, 13 and 14 are also disclosed.

[0120] As used herein, the terms "about" and "at or about" mean that the amount or value discussed can be a specified value, an approximate specified value, or about the same as a specified value. It is generally understood that as used herein, unless otherwise indicated or inferred, the nominal value indicates a variation of ±10%. The term is intended to convey that similar values ​​promote equivalent results or effects described in the claims. That is, it is understood that amounts, sizes, formulations, parameters, and other quantities and properties are not and do not have to be exact, but can be approximate and / or larger or smaller as needed, thereby reflecting tolerances, conversion factors, rounding, measurement errors, etc. and other factors known to those skilled in the art. In general, an amount, size, formulation, parameter, or other quantity or feature is "about" or "approximately", whether or not it is explicitly stated as such. It should be understood that when "about" is used before a quantitative value, unless otherwise specifically stated, the parameter also includes the specific quantitative value itself.

[0121] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances where the event or circumstance occurs and instances where the event or circumstance does not occur. For example, the phrase "optional additional process" means that the additional process may or may not be included, and that the method described includes and does not include the additional process.

[0122] The components used to prepare the compositions of the present disclosure and the compositions themselves used in the methods disclosed herein are disclosed. These and other materials are disclosed herein, and it should be understood that when the combinations, subsets, interactions, groups, etc. of these materials are disclosed, although the specific references of various individual and collective combinations and arrangements of these compounds cannot be explicitly disclosed, each is specifically considered and described herein. For example, if a specific compound is disclosed and discussed, and the multiple modifications that may be made to multiple molecules containing the compound are discussed, then unless specifically indicated to the contrary, each combination and arrangement and possible modifications in the compound are specifically envisioned. Therefore, if a class of molecules A, B and C and a class of molecules D, E and F are disclosed and an example of a combination molecule AD is disclosed, then even if each is not individually narrated, it is still individually and collectively covered, thereby meaning to be considered as a disclosed combination AE, AF, BD, BE, BF, CD, CE and CF. Similarly, any subset or combination of these combinations is also disclosed. Therefore, for example, it is considered to disclose a subgroup of AE, BF and CE. This concept applies to all aspects of the application, including but not limited to the steps in the method for making and using the disclosed composition. Thus, if there are a variety of additional steps that can be performed, it should be understood that each of these additional steps can be performed with any specific aspect or combination of aspects of the methods of the present disclosure.

[0123] References in the specification and the claims that follow to parts by weight of a particular element or component in a composition or article indicate the weight relationship of the element or component to any other element or component in the composition or article, for which parts are expressed. Thus, in a compound containing 2 parts by weight of component X and 5 parts by weight of component Y, X and Y are present in a weight ratio of 2:5, and are present in such a ratio regardless of whether the compound contains additional components.

[0124] Unless specifically indicated to the contrary, weight percentages of components are based on the total weight of the formulation or composition in which the component is included.

[0125] As used herein, "polycarbonate" refers to an oligomer or polymer comprising one or more dihydroxy compounds, such as residues of dihydroxy aromatic compounds, linked by carbonate bonds; it also encompasses homopolycarbonates, copolycarbonates and (co)polyester carbonates.

[0126] Throughout the specification, the terms "residue" and "structural unit" are used synonymously with respect to components of a polymer.

[0127] Unless otherwise specified, as used herein, the terms "weight percent", "wt%" and "wt.%" are used interchangeably to indicate the weight percentage of a given component based on the total weight of the composition. That is, unless otherwise specified, all wt% values ​​are based on the total weight of the composition. It should be understood that the sum of the wt% values ​​of all components in the disclosed composition or formulation is 100.

[0128] Unless otherwise stated to the contrary herein, all test standards are the most recent standards in effect at the time this application was filed.

[0129] Each of the materials disclosed herein is commercially available and / or its production methods are known to those skilled in the art.

[0130] It is understood that the compositions disclosed herein have certain functions. Certain structural requirements are disclosed herein for performing the disclosed functions, and it is understood that there are various structures that can perform the same functions associated with the disclosed structures, and these structures will generally achieve the same results.

[0131] Aspects of the Disclosure

[0132] In various aspects, the present disclosure relates to and includes at least the following aspects.

[0133] Aspect 1. A composite comprising: about 50 wt.% to about 90 wt.% of a thermoplastic resin, wherein the thermoplastic resin comprises a polycarbonate polysiloxane copolymer; and about 10 wt.% to about 50 wt.% of a carbon-based filler, wherein the composite exhibits a dielectric constant ε′ between 5 and 20 and a dissipation loss ε″ between 0.1 and 6 measured at a frequency between about 10 GHz and about 120 GHz, and wherein the combined weight percentage values ​​of all components do not exceed 100 wt.%, and all weight percentage values ​​are based on the total weight of the composite.

[0134] Aspect 2. The composite of aspect 1, wherein the composite has a dissipation factor (Df) of about 0.003 to about 1 when determined as a ratio of ε″ to ε′ measured in transmission mode.

[0135] Aspect 3. The composite according to aspect 1 or 2, wherein a 3.175 mm thick molded plaque comprising the composite absorbs at least 20% of incident microwave radiation at frequencies of 15 GHz to 30 GHz, and absorbs at least 50% of incident microwave radiation at frequencies of 70 GHz to 120 GHz.

[0136] Aspect 4. The composite of aspect 1, wherein the ratio of thermoplastic resin to carbon-based filler is from about 9 to about 1, such that the composite has a surface (volume) resistivity greater than 100 ohms / square (1,000 Ohm.cm).

[0137] Aspect 5. The composite of aspect 1, wherein the thermoplastic resin comprises a semi-crystalline resin or an amorphous resin.

[0138] Aspect 6. The composite of aspect 1, wherein the composite comprises about 10 wt. % to about 50 wt. % of a carbon-based filler.

[0139] Aspect 7. The composite according to aspect 1, wherein the thermoplastic resin comprises polycarbonate, polyetherimide, polyphenylene ether, polystyrene, polysulfone, polyester, polyamide, copolymers thereof, or combinations thereof.

[0140] Aspect 8. The composite of aspect 1, wherein the polycarbonate polysiloxane copolymer is present in an amount of 10 wt. % to about 40 wt. %, based on the total weight of the composite.

[0141] Aspect 9. The composite of aspect 1, wherein the polycarbonate polysiloxane copolymer has a siloxane content of about 5 wt.% to about 50 wt.%, based on the total weight of the polycarbonate polysiloxane copolymer.

[0142] Aspect 10. The composite of aspect 6, wherein the polycarbonate polysiloxane copolymer has a siloxane content of about 20 wt.%.

[0143] Aspect 11. The composite according to aspect 1, wherein the composite is suitable for microwave shielding applications or microwave absorption applications.

[0144] Aspect 12. The composite of aspect 1, wherein a molded panel comprising the composite exhibits microwave absorption and shielding effectiveness.

[0145] Aspect 13. The composite of aspect 1, wherein the carbon-based filler comprises carbon fibers, carbon powder, graphite, graphene, carbon flakes, carbon nanotubes, or combinations thereof.

[0146] Aspect 14. The composite of aspect 1, wherein the carbon-based filler comprises carbon powder.

[0147] Aspect 15. The composite of aspect 1, wherein the carbon-based filler comprises carbon powder and is free of or substantially free of carbon nanotubes, carbon flakes, or carbon fibers.

[0148] Aspect 16. The composite of aspect 1, wherein the composite is a component of an automotive radar sensor.

[0149] Aspect 17. The composite of aspect 1, wherein the composite is a microwave absorbing device or a component thereof.

[0150] Aspect 18. The composite according to aspect 1, further comprising an additive material selected from the group consisting of: antioxidant; colorant; de-molding agent; dye; flow promoter; flow modifier; light stabilizer; lubricant; mold release agent; pigment; colorant; quencher; heat stabilizer; ultraviolet (UV) absorber; UV reflector; UV stabilizer; epoxy resin chain extender; flame retardant; and combinations thereof.

[0151] Aspect 19. An automatic radar sensor for electromagnetic radiation, comprising a composite, the composite comprising: about 50 wt.% to about 90 wt.% of a thermoplastic resin, wherein the thermoplastic resin comprises a polycarbonate polysiloxane copolymer; and about 10 wt.% to about 50 wt.% of a carbon-based filler, wherein the composite exhibits a dielectric constant ε′ between 5 and 20 and a dissipation loss ε″ between 0.1 and 6 measured at a frequency between about 10 GHz and about 120 GHz, and wherein the combined weight percentage values ​​of all components do not exceed 100 wt.%, and all weight percentage values ​​are based on the total weight of the composite.

[0152] Aspect 20. A composite according to any one of Aspects 1 to 8, wherein a molded panel comprising the composite exhibits a microwave attenuation of at least about -1 dB / cm in the K-band and a microwave attenuation of at least -5 dB / cm in the W-band when measured according to a free space method, and exhibits a total shielding effectiveness of at least about 1 dB in the K-band and a total shielding effectiveness of at least 5 dB in the W-band.

[0153] Aspect 21. The composite according to any one of aspects 1 to 18, wherein the percent absorption measured in transmission mode is at least 70%, and wherein the carbon-based filler is present in an amount of 12 wt.% to 16 wt.% at 77 GHz.

[0154] Aspect 22. The composite according to any one of aspects 1 to 18, wherein the percent absorption measured in transmission mode is at least 70%, and wherein the carbon-based filler is present in an amount of 14 wt.% to 18 wt.% at 110 GHz.

[0155] Aspect 23. A composite according to any one of Aspects 1 to 18, wherein the absorption percentage measured in transmission mode is at least 70%, and wherein 1) the carbon-based filler is present in an amount of 12 wt.% to 16 wt.% at 77 GHz, and 2) the carbon-based filler is present in an amount of 14 wt.% to 18 wt.% at 110 GHz.

[0156] Examples

[0157] The following examples are presented to provide a complete disclosure and description of how to make and evaluate the compounds, compositions, articles, devices and / or methods claimed herein to those skilled in the art, and are intended to be used as examples only and are not intended to limit the present disclosure. Efforts have been made to ensure accuracy with respect to numbers (e.g., amounts, temperatures, etc.), but some errors and deviations should be considered. Unless otherwise indicated, parts are parts by weight, temperatures are in ° C or at ambient temperature, and pressures are at or near atmospheric pressure. Unless otherwise indicated, percentages of compositions mentioned are in terms of wt%.

[0158] There are many variations and combinations of mixing conditions, such as component concentrations, extruder design, feed rate, screw speed, temperature, pressure, and other mixing ranges and conditions that can be used to optimize the product purity and yield obtained from the described process. Only reasonable and routine experimentation will be required to optimize such process conditions.

[0159] Example I: Dielectric properties in the K band

[0160] Various composite samples were prepared. The formulations are presented in Table 1 ( Figure 1 ). The comparative samples comprised a blend of polycarbonate resin and carbon black and were designated as CE1-CE5. The inventive samples combined a blend of polycarbonate resin, carbon black and polysiloxane-polycarbonate copolymer. The composite samples were prepared on a co-rotating twin-screw extruder with a diameter of 40 mm, wherein the ingredients of the different formulations were added to the extruder, melted, mixed and pushed out of the extruder through a six-hole die plate. The extruder was operated at a screw speed of 325 rpm, a rate of 45 pounds per hour (0.0225 tons per hour) and a torque of 50-60% of the maximum torque. The extruder barrel temperature was maintained between about 180-195°C (upstream, the feed throat of the extruder) and 285-305°C (downstream, the die plate of the extruder). The die plate temperature was maintained between 285-295°C, and the melt temperature leaving the extruder was measured to be between 310-320°C.

[0161] The surface resistivity and volume resistivity of the comparative sample and the sample of the present invention were observed at room temperature, measured according to ASTM D257 on a 4 inch x 5 inch and 1 / 8 inch thick (10.2 cm x 12.7 cm and 0.32 cm thick) molded plate under the environmental conditions of 10-100 V voltage range, 50% relative humidity (RH) and 23° C. The values ​​are presented in Table 2 ( Figure 2 )middle. Figure 3 A graphical representation of the volume resistivity of CE1-5 and E1-5 is shown. As shown, the resistivity of the comparative and inventive samples is comparable, with the values ​​for E1-E5 being generally lower, with the exception of CE5 and E5. Figure 4 Shown is a graphical representation of the volume resistivity of the samples as the carbon black loading is adjusted.

[0162] The dielectric constant values ​​(dielectric constant ε′ and dissipative losses ε″) were also observed according to the free space method. The free space method consists of a vector network analyzer connected to two antennas (transmitting antenna and receiving antenna) to focus microwave energy at or through a piece of material. The method can be operated in transmission mode (allowing all three energy transfer modes, transmission, absorption and reflection) or metal backed reflection mode (allowing only absorption and reflection, where transmission is suppressed by using a metal plate behind the sample). This method is non-contact and is particularly suitable for millimeter wave frequencies.

[0163] The samples were evaluated in two modes: (a) transmission mode and (b) metal backing reflection mode as presented in FIG5 . Figure 6 The dielectric constants (ε′, real part) observed for CE1-CE5 and E1-E5 at frequencies from 18 to 26.5 GHz are provided. As demonstrated, increasing the amount of carbon black increases the value of the dielectric constant. Surprisingly, the presence of the polysiloxane copolymer also increases the dielectric constant at the same loading of carbon black. (Compare CE1 to E1, CE2 to E2, etc.). Figure 7 A graphical representation of the dielectric loss (ε″, imaginary part) of CE1-CE5 and E1-E5 is provided. As shown, as the amount of carbon black in the composite increases, the dielectric loss increases. Similarly, at the same loading of carbon black, the presence of the polysiloxane copolymer also increases the dielectric loss of the material.

[0164] Figure 8The metal backing reflection front face measurement results are shown with the return loss specified in decibels (dB). The return loss (also called reflection loss) indicates the proportion of microwaves that are rejected (reflected) compared to the microwaves that are accepted that reach the antenna. For example, a reflection loss of 0 dB would mean that there is no reflection loss and 100% of the incident radiation would be reflected back to the transmitting antenna. This would be the behavior exhibited by a perfect microwave radiation mirror (100% MW radiation reflector). The reflection loss values ​​of metals (stainless steel, aluminum, etc.) are close to 0 dB. Similarly, the more negative the value of the reflection loss, the more the material absorbs MW radiation (because there is a metal plate behind the sample during the measurement, and the transmittance is also zero in the metal backing reflection mode). As shown, as the amount of carbon black increases (CE1 to CE5 and E1 to E5), the reflection loss (or microwave absorption) increases to a certain point and then decreases. Moreover, as the carbon black content increases, the resonant frequency of maximum absorption shifts to lower frequencies. For CE1-CE5 without polysiloxane-polycarbonate copolymer and E1-E5 with polysiloxane-polycarbonate copolymer, the trend is clear. Fig. 9 Metal backing reflection back side measurements with return loss specified in decibels (dB) are shown. A similar trend is observed for the back side measurements. As shown, with increasing amounts of carbon black (CE1 to CE5 and E1 to E5), the reflection loss (or microwave absorption) increases to a certain point and then decreases. Figure 8 (front side of the board) and Fig. 9 (Back side of board) These dielectric measurements are shown to be consistent from front to back and are reproducible using the free space method used to characterize the materials of the present invention.

[0165] Fig.10 Provides a graphical representation of the attenuation constant in decibels per centimeter of sample thickness. With increasing carbon black content, the attenuation characteristics of the composite samples increase. Refer to CE1 to CE5 and E1 to E5. With increasing carbon, the attenuation increases. With increasing amounts of siloxane (for the same amount of carbon), the attenuation increases (more negative values), thereby indicating energy losses, i.e., energy decay within the material. Fig.11 The total shielding effectiveness in decibels is provided. As the carbon black content increases, the shielding effectiveness of the composite increases. Shielding effectiveness describes the combined effect of absorption and reflection of a material. Surprisingly, at the same carbon black loading, the shielding effectiveness of the inventive sample with the polysiloxane-polycarbonate copolymer is higher than the shielding effectiveness of the corresponding comparative sample without the copolymer.

[0166] Fig.12The percentage of power absorbed in transmission mode, determined according to the free space method, is presented. In transmission mode, the total microwave energy absorbed by the material increases with increasing carbon black content for most frequencies studied. For most frequencies observed, the presence of polysiloxane-polycarbonate copolymer increases the total microwave energy absorbed by the composite at the same carbon black loading. Fig.13 These absorption results are provided for the metal backing reflection mode.In the metal backing reflection mode, as the amount of carbon black increases from CE1-CE5 and E1-E5, the absorbed microwave energy increases to a certain level and then decreases.

[0167] Example II: Dielectric Properties in the W-Band (75-110 GHz)

[0168] The dielectric constant values ​​(dielectric constant ε′ and dissipation loss ε″) were also observed according to the free space method. The values ​​in Table 1 ( Figure 1 ) in the formulation. For the front side of the molded plate having the aforementioned dimensions, the real and imaginary dielectric constants were observed and presented in Fig.14 middle. Fig.15 Metal backed reflective front face measurements are shown with return loss specified in decibels (dB).

[0169] Fig.16 and 17 Graphical representations of the attenuation constant and total shielding effectiveness are provided separately.

[0170] The average thickness of the molded panels is presented in Table 3 below.

[0171] Average sample thickness (mm) CE1 3.442 CE2 3.489 CE3 3.381 CE4 3.418 CE5 3.325 E1 3.320 E2 3.355 E3 3.316 E4 3.261 E5 3.252

[0172] Fig.18 The power percentage measured in transmission for sample CE1 is shown. Fig.19 The power percentage measured in transmission for sample CE2 is shown. Fig. 20 The power percentage measured in transmission for sample CE3 is shown. Fig.21 The power percentage measured in transmission for sample CE4 is shown. Fig. 22 The power percentage measured in transmission for sample CE5 is shown. Fig.23 The power percentage measured in transmission for sample E1 is shown. Fig.24 The power percentage measured in transmission for sample E2 is shown. Fig.25 The power percentage measured in transmission for sample E3 is shown. Fig.26 The power percentage measured in transmission for sample E4 is shown. Fig. 27The power percentage measured in transmission for sample E5 is shown.

[0173] As carbon loading increases, absorption increases to a certain point and then decreases or remains fairly constant. Reflection increases slightly with increasing carbon loading (from about 20% to about 30%). Since the sum of absorption, reflection, and transmission at each frequency must amount to 100% of the incident MW radiation, transmittance must decrease with increasing carbon black content, as shown in the graph (from about 20% transmission in CE1 to about 1-2% transmission in CE5). Similar conclusions can be drawn from E1 to E5.

[0174] Tables 4A and 4B ( Fig.28A and 28B ) shows the values ​​of real and imaginary dielectric constants, dissipation factor, attenuation constant, total shielding effectiveness, power in transmission mode and absorbed power for E1 to E5 at 77 GHz and 110 GHz, respectively. Figures 29A to 29F It is a graphical representation of the real and imaginary dielectric constants, dissipation factor, attenuation constant, total shielding effectiveness, power in transmission mode, and absorbed power for E1 to E5 at 77 GHz. Figures 30A to 30F is a graphical representation of the real and imaginary dielectric constants, dissipation factor, attenuation constant, total shielding effectiveness, power in transmission mode and power absorbed for E1 to E5 at 110 GHz. These data show that there is a maximum in microwave absorption over the range of carbon concentrations studied (12 to 20 wt%). However, this maximum occurs at different concentrations of carbon black, depending on the frequency of the incident radiation. More specifically, for 77 GHz, the maximum occurs at about 14 wt%, and for 110 GHz, the maximum occurs at about 16 wt%. The maximum microwave absorptivity also depends on the frequency studied and is found to be about 72% at 77 GHz and about 77.5% at 110 GHz.

[0175] As provided herein, both the carbon black concentration for maximum microwave absorptivity and the maximum microwave absorptivity depend on the frequency of the incident radiation: both of these quantities increase with increasing frequency, from 14 wt % carbon and 72% MW absorptivity at 77 GHz to 16 wt % carbon and 77.5% MW absorptivity at 110 GHz.

[0176] If these results are compared with the previously disclosed TM The results of the 360G carbon powder mixture composition were compared to those of the ENSACO TM With 360G carbon, the carbon black concentration for maximum MW absorption is only 4 wt%. Using ENSACO TM360G and ENSACO TM BET (Brunauer, Emmett and Teller, m2 / g) of two carbon blacks at 250 g 2 / g)) surface area and oil absorption value (OAN, milliliters per 100 grams (ml / 100g)) are significantly different, as shown in Table 5 below (pour density, kilograms per cubic meter (kg / m 3 ). It is worth noting that ENSACO TM 350G and ENSACO TM 360G has these properties but is manufactured using a different process. These results indicate that the carbon black concentration for maximum MW absorption is highly dependent on the type of MW absorbing carbon used in the formulation.

[0177] Table 5: Types of carbon black and their corresponding properties.

[0178]

[0179]

[0180] The above description is intended to be illustrative and not restrictive. For example, the above examples (or one or more aspects thereof) can be used in combination with each other. After reviewing the above description, other embodiments can be used by those of ordinary skill in the art. An abstract is provided to allow readers to quickly determine the nature of the present technology disclosure. The abstract is submitted based on the understanding that it will not be used to interpret or limit the scope or meaning of the claims. Moreover, in the above specific embodiments, various features can be grouped together to simplify the present disclosure. This situation should not be interpreted as intended to be necessary for any claim to disclose features that are not required for protection. On the contrary, the subject matter of the present invention may be less than all the features of a specific disclosed embodiment. Therefore, the attached claims are hereby incorporated into the specific embodiments as examples or embodiments, wherein each claim exists alone as a separate embodiment, and it is expected that such embodiments can be combined with each other into various combinations or arrangements. The scope of the present disclosure should be determined with reference to the attached claims and the full scope of equivalents granted by this claim.

[0181] It will be apparent to those skilled in the art that various modifications and variations may be made in the present disclosure without departing from the scope or spirit of the present disclosure. Other embodiments of the present disclosure will be apparent to those skilled in the art by consideration of this specification and practice of the disclosure disclosed herein. The description and examples are intended to be considered exemplary only, with the true scope and spirit of the present disclosure being indicated by the following claims.

[0182] The patentable scope of the disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims or if they include equivalent structural elements with insubstantial differences from the literal language of the claims.

Claims

1. A composite comprising: 50 wt.% to 90 wt.% of a thermoplastic resin, the thermoplastic resin comprising Polycarbonate homopolymer, and 10 wt. % to 40 wt. % of a polycarbonate-polysiloxane copolymer, based on the total weight of the composite; and Carbon black, wherein the composite exhibits a dielectric constant ε' between 5 and 20 and a dissipation loss ε" between 0.1 and 6, measured at a frequency between 10 GHz and 120 GHz, and The combined weight percentage values ​​of all components do not exceed 100 wt.%, and all weight percentage values ​​are based on the total weight of the composite, and The complex comprises 12 wt.% to 16 wt.% of said carbon black, and an absorption percentage measured in transmission mode at 77 GHz of at least 70%, or 14 wt.% to 18 wt.% of said carbon black, and an absorption percentage measured in transmission mode at 110 GHz of at least 70%.

2. The composite of claim 1, wherein a 3.175 mm thick molded plaque comprising the composite absorbs at least 20% of incident microwave radiation at frequencies of 15 GHz to 30 GHz and at least 50% of incident microwave radiation at frequencies of 70 GHz to 120 GHz.

3. The composite of claim 1, wherein the composite has a surface resistivity greater than 100 ohms / square.

4. The composite of claim 1, wherein the thermoplastic resin comprises polycarbonate, polyetherimide, polyphenylene oxide, polystyrene, polysulfone, polyester, polyamide, copolymers thereof, or combinations thereof.

5. The composite according to any one of claims 1 to 4, wherein the polycarbonate polysiloxane copolymer has a siloxane content of 5 wt.% to 30 wt.%, based on the total weight of the polycarbonate polysiloxane copolymer.

6. The composite of any one of claims 1 to 4, wherein a molded panel comprising the composite exhibits a microwave attenuation of at least -1 dB / cm in the K-band and a microwave attenuation of at least -5 dB / cm in the W-band when measured according to a free space method, and exhibits a total shielding effectiveness of at least 1 dB in the K-band and a total shielding effectiveness of at least 5 dB in the W-band.

7. The composite of any one of claims 1 to 4, wherein the composite is free of carbon nanotubes, carbon flakes or carbon fibers.

8. The composite of any one of claims 1 to 4, wherein the composite is a component of an automotive radar sensor.

9. The composite of any one of claims 1 to 4, wherein the composite is a microwave absorbing device or a component thereof.

10. The composite of any one of claims 1 to 4, further comprising an additive material selected from the group consisting of: antioxidants; dyes; flow modifiers; light stabilizers; lubricants; mold release agents; pigments; colorants; quenchers; heat stabilizers; ultraviolet (UV) absorbers; UV reflectors; epoxy resin chain extenders; flame retardants; and combinations thereof.

11. The composite of any one of claims 1 to 4, wherein the carbon black comprises conductive carbon black.

12. An automatic radar sensor for electromagnetic radiation, comprising a composite, said composite comprising: 50 wt.% to 90 wt.% of a thermoplastic resin, the thermoplastic resin comprising Polycarbonate homopolymer, and 10 wt. % to 40 wt. % of a polycarbonate-polysiloxane copolymer, based on the total weight of the composite; and Carbon black, wherein the composite exhibits a dielectric constant ε' between 5 and 20 and a dissipation loss ε" between 0.1 and 6, measured at a frequency between 10 GHz and 120 GHz, and The combined weight percentage values ​​of all components do not exceed 100 wt.%, and all weight percentage values ​​are based on the total weight of the composite, and The complex comprises 12 wt.% to 16 wt.% of said carbon black, and an absorption percentage measured in transmission mode at 77 GHz of at least 70%, or 14 wt.% to 18 wt.% of said carbon black, and an absorption percentage measured in transmission mode at 110 GHz of at least 70%.

13. The automatic radar sensor of claim 12, wherein the carbon black comprises conductive carbon black.

Citation Information

Patent Citations

  • Polymer blends of polycarbonate-polysiloxane block copolymers with polycarbonates and polyestercarbonate copolymers

    EP0524731A1

  • Method of preparing transparent silicone-containing copolycarbonates

    US20040039145A1

  • Siloxane bischloroformates

    US6723864B2

  • Polycarbonate composition and articles formed therefrom

    CN104204060A

  • Reinforced flame retardant polycarbonate composition and molded article comprising same

    CN105849192A